Efficacy of allogeneic cord blood platelet gel on wounds of dystrophic epidermolysis bullosa patients after pseudosyndactyly surgery. Issue 1 (19th October 2020) - Torkamaniha, Elham; Amirkhani, Mohammad Amir; Dahmardehei, Mostafa; Rebulla, Paolo; Piccin, Andrea; Hortamani, Shamim; Heidari‐Kharaji, Maryam; Mansouri, Parvin; Hamidieh, Amir Ali; Nilforoushzadeh, Mohammad Ali
Abstract: Epidermolysis bullosa (EB) is a rare genetic disorder characterized by the formation of blisters and wounds in skin and mucous membranes; it is classified into four types and has various methods of treatment. Management of previous wounds and prevention of formation of new lesions are the most important strategies in the course of therapy to improve patient's quality of life; lack of wound management can lead to further complications such as infection. The current study investigated the therapeutic effects of allogeneic platelet gel (prepared from umbilical cord blood) in a group of children diagnosed with dystrophic epidermolysis bullosa (DEB) eligible for surgical correction of pseudosyndactyly in the hand. The post‐surgical clinical outcome in this group was compared with the clinical outcomes of DEB patients receiving the standard treatment (paraffin gauze wound dressing and topical antibiotics) after corrective surgery. The current study results showed an increase in the rate of recovery and promotion of tissue granulation, complete wound healing, and a decrease in pain level and treatment period. The application of cord blood platelet gel topical dressing was not a conventional method of treatment in patients with DEB wounds and blisters. However, the current study results demonstrated that this gel dressing could effectively accelerate epithelialization and healing of the wounds and decrease patients' pain and post‐surgical recovery period, which altogether leads to improvements in patients' overall quality of life.